Diagnosis for Pheochromocytoma and Paraganglioma: A Joint Position Statement of the Korean Pheochromocytoma and Paraganglioma Task Force - Ku, Eu Jeong; Kim, Kyoung Jin; Kim, Jung Hee; Kim, Mi Kyung; Ahn, Chang Ho; Lee, Kyung Ae; Lee, Seung Hun; Lee, You-Bin; Park, Kyeong Hye; Choi, Yun Mi; Hong, Namki; Hong, A Ram; et al. (Endocrinology and metabolism (Seoul), 2021)
Pheochromocytoma and paraganglioma (PPGLs) are rare catecholamine-secreting neuroendocrine tumors but can be life-threatening. Although most PPGLs are benign, approximately 10% have metastatic potential. Approximately 40% cases are reported as harboring germline mutations. Therefore, timely and accurate diagnosis of PPGLs is crucial. For more than 130 years, clinical, molecular, biochemical, radiological, and pathological investigations have been rapidly advanced in the field of PPGLs. However, performing diagnostic studies to localize lesions and detect metastatic potential can be still challenging and complicated. Furthermore, great progress on genetics has shifted the paradigm of genetic testing of PPGLs. The Korean PPGL task force team consisting of the Korean Endocrine Society, the Korean Surgical Society, the Korean Society of Nuclear Medicine, the Korean Society of Pathologists, and the Korean Society of Laboratory Medicine has developed this position statement focusing on the comprehensive and updated diagnosis for PPGLs.